Vaulting to victory - Yu, Bill (Get in the game (Magic Wagon (Firm)), 2019)
Isabella is the best gymnast at her school, until Morgan--Isabella's archrival who continually beats her at all the meets--transfers her school and takes Isabella's team captain spot. Isabella is furious, but Morgan proves that there's more to rivalries than just the drama.